Amino acids as nutritional factors and (p)ppGpp as an alarmone of the stringent response regulate natural transformation in Micrococcus luteus - Lichev, Antoni (Sci Rep, 2019)
Natural competence for genetic transformation refers to the natural ability of various bacteria to take up exogenous DNA from their surroundings and to incorporate internalized genetic information into their genomes. By promoting bacterial diversification and adaptability, this process represents a major driving force in bacterial evolution. Micrococcus luteus was one of the first organisms used to study natural transformation in bacteria. Since then, however, only very little information about this phenomenon has been reported in M. luteus or in any member of the Actinobacteria phylum (low-GC Gram-positive bacteria). Previous work in our group indicated major differences between the transformation apparatus of M. luteus and the transformation machinery described for various Gram-negative and Gram-positive model bacteria belonging to the phyla Proteobacteria and Firmicutes (high-GC Gram-positive bacteria). This prompted us to initiate a study concerning the regulation mechanism of competence development in M. luteus. In this report, we identify amino acids as a nutritional factor that influences competence in a concentration-dependent manner. By using a transcriptional reporter strain for one of the late competence genes, we demonstrate how increasing concentrations of both amino acids mixtures and single amino acids supplemented to the growth medium affect transformability on transcriptional and post-transcriptional level. Furthermore, we revisit previously generated auxotrophic mutants to show that the transformation machinery is turned down during a state of extreme hunger for amino acids presumably as a part of a general response to auxotrophy. Finally, by generating and analysing knockout mutants for two predicted stringent response enzymes, we provide evidence for the involvement of the alarmone (p)ppGpp as a putative mediator of the effects on transformation development caused by amino acids. As a member of the Actinobacteria phylum, M. luteus could serve as a model for other representatives of the phylum, including a number of important human pathogens.